A comparative study on determination of the equilibrium, kinetic and thermodynamic parameters of biosorption of copper(II) and lead(II) ions onto pretreated Aspergillus niger - Dursun, AY (Elsevier Science Sa, 2006)
The kinetics and thermodynamics of copper(II) and lead(H) biosorption onto Aspergillus niger pretreated with NaOH were studied with respect to pH, temperature and initial metal ion concentration. The optimum pH values were determined as 5.0 and 4.0 for copper(II) and lead(II) at 25 degrees C, respectively. Biosorption capacity values of the biomass increased with increasing initial metal ion concentration and temperature. The maximum biosorption capacities were obtained as 28.7 and 32.6 ing g(-1) at 250 mg dm(-3) initial copper(H) and lead(II) concentration at 35 degrees C, respectively. The equilibrium data were analyzed using Freundlich, Langmuir and Redlich-Peterson adsorption models. The model parameters were estimated by the non-linear regression analysis. It was seen that equilibrium data fitted very well to the Langmuir adsorption model at all temperatures studied. The applicability of the saturation type kinetic model for metal-A. niger system was tested at different temperature in the range of 20-35 degrees C. The activation energies of the biosorption were determined as 27.48 and 36.76 kJ mol(-1) for Cu(II) and Pb(II)-A. niger systems, respectively. Using the thermodynamic equilibrium coefficients obtained at different temperature. the Gibbs free energy changes (- 18.97 kJ mol-1 for Cu(II) and -22.97 kJ mol(-1) for Pb(II) (at 35 degrees C)), enthalpy changes (28.9 kJ mol(-1) for Cu(II) and 38.3 kJ mol(-1) for Pb(II)) and entropy changes (0.168 kJ mol(-1) K-1 for Cu(II) and 0.186 kJ mol(-1) K-1 for Pb(II)) of biosorption were also determined. The results showed that biosorption of copper(II) and lead(II) on A. niger was endothermic and spontaneous. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: biosorption; copper(II); lead(II); Aspergillus niger; adsorption isotherm; saturation type kinetic model; activation energy; Gibbs free energy; enthalpy; entropy